2021
DOI: 10.52082/jssm.2021.300
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Quadriceps Fatigue Induces Greater Impairments of Ipsilateral versus Contralateral Elbow Flexors and Plantar Flexors Performance in Physically Active Young Adults

Abstract: Non-local muscle fatigue (NLMF) studies have examined crossover impairments of maximal voluntary force output in non-exercised, contralateral muscles as well as comparing upper and lower limb muscles. Since prior studies primarily investigated contralateral muscles, the purpose of this study was to compare NLMF effects on elbow flexors (EF) and plantar flexors (PF) force and activation (electromyography: EMG). Secondly, possible differences when testing ipsilateral or contralateral muscles with a single or rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…In line with the previous studies, a decrease in MVC, VA, potentiated force, and sEMG RMS was observed after single-leg knee-extension exercise in both the exercising and non-exercising limb (Gandevia 2001 ; Rattey et al 2006 ; Martin et al 2008 ; Doix et al 2013 ; Elmer et al 2013 ; Kennedy et al 2015 ; Jalal Aboodarda et al 2019 ; Whitten et al 2021 ). The variations in muscle metabolites induced in the exercising limb by the fatiguing exercise, i.e., an increase in intracellular inorganic-P, K + (Johnson et al 2014 ), H + (Bangsbo et al 1996 ; Johnson et al 2014 ), blood lactate concentration (Bangsbo et al 1996 ; Halperin et al 2014 ; Johnson et al 2014 ), and a decrease in Ca 2+ availability (Fitts 1994 ), trigger an increase in group III/IV muscle afferent feedback at both supraspinal and spinal level.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In line with the previous studies, a decrease in MVC, VA, potentiated force, and sEMG RMS was observed after single-leg knee-extension exercise in both the exercising and non-exercising limb (Gandevia 2001 ; Rattey et al 2006 ; Martin et al 2008 ; Doix et al 2013 ; Elmer et al 2013 ; Kennedy et al 2015 ; Jalal Aboodarda et al 2019 ; Whitten et al 2021 ). The variations in muscle metabolites induced in the exercising limb by the fatiguing exercise, i.e., an increase in intracellular inorganic-P, K + (Johnson et al 2014 ), H + (Bangsbo et al 1996 ; Johnson et al 2014 ), blood lactate concentration (Bangsbo et al 1996 ; Halperin et al 2014 ; Johnson et al 2014 ), and a decrease in Ca 2+ availability (Fitts 1994 ), trigger an increase in group III/IV muscle afferent feedback at both supraspinal and spinal level.…”
Section: Discussionsupporting
confidence: 85%
“…The variations in muscle metabolites induced in the exercising limb by the fatiguing exercise, i.e., an increase in intracellular inorganic-P, K + (Johnson et al 2014 ), H + (Bangsbo et al 1996 ; Johnson et al 2014 ), blood lactate concentration (Bangsbo et al 1996 ; Halperin et al 2014 ; Johnson et al 2014 ), and a decrease in Ca 2+ availability (Fitts 1994 ), trigger an increase in group III/IV muscle afferent feedback at both supraspinal and spinal level. This feedback leads to a reduction in motor neuron excitability and firing rate, and results in a motor drive inhibition (Martin et al 2008 ; Kennedy et al 2015 ) toward the exercising limb, and in the contralateral non-exercising limb via neural pathways implicated in the crossover effect phenomenon (Rattey et al 2006 ; Doix et al 2013 ; Laginestra et al 2021 ; Whitten et al 2021 ). In addition to the central mechanisms, the reduction in M-wave and potentiated force in the exercising limb suggests a possible impairment in sarcolemma conduction properties and of cross-bridge cycle efficiency (Hultman et al 1985 ; Cady et al 1989 ; Fitts 1994 ; Bangsbo et al 1996 ; Kent-Braun 1999 ; Halperin et al 2014 ; Johnson et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same occurs with the accumulation of extracellular potassium due to disturbances in the cell’s sodium–potassium pump induced by fatigue [ 42 ]. Furthermore, it has been shown that the replacement of electrolytes is faster than the recovery of PH during fatigue situations, also affecting muscle contractions in a negative form [ 42 , 43 , 44 , 45 ].…”
Section: Etiology Of Central Nervous System and Peripheral Fatiguementioning
confidence: 99%
“…During the prolonged fatiguing contraction, the CV of BB muscle declined during the initial 30% of contraction duration and then increased progressively until the end of the contraction, while the CV of TB muscle showed a continuous decrease tendency for the whole contraction. During sustained isometric contractions, CV has been found to decrease due to factors including an increase in muscle acidosis (Myburgh, 2004;Schmitz et al, 2012), alterations in blood flow (Sj Gaard et al, 1988;Hammer et al, 2020), a decrease in extracellular sodium concentration (Overgaard et al, 1997), and accumulation of extracellular potassium ions (Fortune and Lowery, 2009;Whitten et al, 2021) as a result of peripheral muscle fatigue. On the other hand, CV increases gradually when larger motor units are recruited (Adam and De Luca, 2003).…”
Section: Discussionmentioning
confidence: 99%